Correction of stomach cancer CT attenuation values for variations due to differences in CT imaging conditions through repeated CT scans. - Jeong Min Seo; Sun Young Baek; Woo Kyoung Jeong; Kyoung Doo Song (PLoS ONE)
Purpose To develop methods for correcting variations in CT attenuation values of advanced gastric cancer (AGC) due to differences in CT imaging conditions using repeated pre-treatment CT scans. Methods A total 211 patients (146 men) with AGC who underwent pre-treatment CT twice were included in this retrospective study. The Pearson correlation between the difference in tumor attenuation values measured on both CT scans and the difference in attenuation values of other organs was analyzed. A formula to correct tumor CT attenuation values was developed using univariate linear regression analysis. Results The Pearson correlation coefficient was the highest between the difference in tumor attenuation values and that of the main portal vein (MPV) attenuation values (0.86, P <.01). The formula to correct tumor attenuation values was as follows: calculated tumor attenuation value on CT scan 2 = tumor attenuation value on CT scan 1 - (-3.5 + 0.4 x (MPV attenuation value on CT scan 1 - MPV attenuation value on CT scan 2)). The mean difference between calculated and actual tumor attenuation values was 1.6 HU (SD, 8.7; range -22.5-24.72), with a Pearson correlation coefficient of 0.95 (P <.01). Conclusion Utilizing the attenuation value of the MPV allows for correction of variations in tumor attenuation values caused by different CT imaging conditions, enabling the prediction of reproducible tumor attenuation in patients with AGC. Future studies are needed to validate these findings and address the study's limitations, including its retrospective design and the absence of unenhanced CT data. Advances in knowledge The attenuation value of the MPV can be used to predict reproducible tumor attenuation values in gastric cancer.